John Spinks, 1964. - (:unkn) unknown (Forsyth County Public Library, 2008)
WSJ 4-12-64 p.C14.
John Spinks, 1964. The photo was used for a feature on men's hats.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth